PERTANGGUNGJAWABAN PIDANA ANAK PELAKU TINDAK PIDANA PERSETUBUHAN SECARA BERSAMA-SAMA (PUTUSAN NO. 18/PID.SUS-ANAK/2021/PN SRG): Criminal Responsibilities Of Children Who Commit The Crime Of Sexual Intercourse Together (Study Of Decisions Number 18/Criminal.Specific-Children/2021/District Court.Serang) - Margaretha, Rade Dian; Widjajanti, Ermania (AMICUS CURIAE, 2024)
Criminal responsibility does not only apply to adults in general, but can also apply to children as perpetrators. Criminal responsibility for children is based on the maximum age limit of the child himself. The writing of this article examines Decision No. 18/Pid.Sus-Anak/2021/PN Srg. The formulation of the problem in the research is how the form of criminal liability of children and the form of participation in the case of joint child sexual intercourse. In the preparation of this article, the author uses normative legal research methods, with the nature of analytical descriptive research. In the preparation of this article using secondary data. The method used is qualitative method. The results of the research analysis are that the two child perpetrators can be held criminally responsible, which they are subject to Article 82 Paragraph (1) of Act Number 17, 2016, with imprisonment for 1 year and 8 months. The form of participation imposed on the two child perpetrators is participation in committing (medepleger), with the condition of physical action as evidenced by the two child perpetrators inviting the victim to go to boarding houses by force, then committing a series of acts of sexual intercourse and fornication, as well as the condition of awareness of cooperation as evidenced by the cooperation of the two child perpetrators to invite the victim to join the two child perpetrators.